Teori Pendekatan dan Model Kepemimpinan dalam Lembaga Pendidikan - Sukataman Sukataman; Muhibbatun Soodiqoh; Farkhah ‘Azizah .; M Husein Falaakhuddin (LPPM IAINU Kebumen, 2023)
This journal discusses the approaches and models of leadership in an institution or organization that we often encounter. The purpose of writing this journal is to find out and understand and implement knowledge about leadership approaches and models that are much needed in educational institutions, both formal, informal and non-formal. Writing this journal in order to add insight to students and students in studying leadership. This is very important and will be experienced by students and students. Because by studying this journal it is able to prepare and shape leadership character with various approaches and leadership models that can adapt to the circumstances of society. So it can be easily accepted. A person's leadership greatly influences other people, especially his subordinates. There are four leadership approaches, namely: (1) the power influence approach (2) the Traid Approach, (3) the Behavioral Approach, (4) the Situational Approach. Approach is also closely related to the leadership model.